Pendidikan Keluarga, Saving Attitudes dan Perencanaan Pensiun: Studi Pada Badan Penyelenggara Jaminan Sosial Kesehatan di Kota Tondano [Family Education, Saving Attitudes and Retirement Planning: Study of Badan Penyelenggara Jaminan Sosial Kesehatan in Tondano City] - Tiwow, Rafianty; Wuryaningrat, Nikolas F.; Winerungan, Robert R. (Feedforward: Journal of Human Resource, 2022)
This study aims to determine the effect of family education on retirement planning at the Tondano Branch Health BPSJS office, the effect of saving attitudes on retirement planning at the Tondano Health BPSJS office, and the influence of family education and saving attitudes towards retirement planning at the BPSJS office. Tondano Health Branch. This study is a causal associative study with a population of 35 members. The number of samples of 35 people was taken using a saturated sampling technique. Methods of data collection using questionnaires and documentation. The data analysis technique used multiple regression. The results of this study indicate that there is a positive and significant effect of family education on retirement planning at the Tondano Branch Health BPSJS office, that there is a positive and significant influence on saving attitudes towards retirement planning at the Tondano Branch Health BPSJS office, and that there is a positive and significant effect, and significant influence of family education and saving attitudes towards retirement planning at the health BPSJS office Tondano Branch. The effective contribution of family education variables and saving attitudes is 82.1% towards retirement planning.BAHASA INDONESIA ABSTRACTPenelitian ini bertujuan untuk mengetahui pengaruh pendidikan keluarga terhadap perencanaan pensiun di kantor BPSJS Kesehatan Cabang Tondano, pengaruh sikap menabung terhadap perencanaan pensiun di kantor BPSJS Kesehatan Tondano, dan pengaruh pendidikan keluarga dan sikap menabung terhadap perencanaan pensiun pada kantor BPJS Cabang Kesehatan Tondano. Penelitian ini merupakan penelitian asosiatif kausal dengan jumlah populasi 35 orang. Jumlah sampel 35 orang diambil dengan menggunakan teknik sampling jenuh. Metode pengumpulan data menggunakan angket dan dokumentasi. Teknik analisis data menggunakan regresi berganda. Hasil penelitian ini menunjukkan ada pengaruh positif dan signifikan pendidikan keluarga terhadap perencanaan pensiun di kantor BPSJS Kesehatan Cabang Tondano, ada pengaruh positif dan signifikan sikap menabung terhadap perencanaan pensiun di kantor BPSJS Kesehatan Cabang Tondano, dan ada merupakan pengaruh yang positif dan signifikan, dan ada pengaruh signifikan pendidikan keluarga dan sikap menabung terhadap perencanaan pensiun di BPSJS kesehatan Cabang Tondano. Kontribusi efektif variabel pendidikan keluarga dan sikap menabung sebesar 82,1% terhadap perencanaan pensiun.